2017
DOI: 10.1515/pjmpe-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Patient dose measurement in common medical X-ray examinations and propose the first local dose reference levels to diagnostic radiology in Iran

Abstract: Introduction: The main purpose of this study was to investigate patient dose in pelvic and abdomen x-ray examinations. This work also provided the LDRLs (local diagnostic reference levels) in Khuzestan region, southwest of Iran to help establish the NDRLs (national diagnostic reference levels). Methods: Patient doses were assessed from patient's anatomical data and exposure parameters based on the IAEA indirect dosimetry method. With regard to this method, exposure parameters such as tube output, kVp, mAs, FFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The minimum and the maximum tube loading (mAs) that were used for AP pelvis radiography is (13.6-35.38 mAs). The current average values of the mAs are almost similar to those reported in literature [6][7][8][9][10]. The SID recorded for AP pelvis radiography is ranged from 100 cm 123 cm.…”
Section: Table 3 This Table Lists the X-ray Tube Output Factors Meassupporting
confidence: 83%
See 1 more Smart Citation
“…The minimum and the maximum tube loading (mAs) that were used for AP pelvis radiography is (13.6-35.38 mAs). The current average values of the mAs are almost similar to those reported in literature [6][7][8][9][10]. The SID recorded for AP pelvis radiography is ranged from 100 cm 123 cm.…”
Section: Table 3 This Table Lists the X-ray Tube Output Factors Meassupporting
confidence: 83%
“…Therefore, protecting patients gonads from unnecessary radiation dose is paramount during anterior-posterior (AP) pelvis radiography. Measurement of patient dose during AP pelvis X-ray examination was one of the aims of many researches [7][8][9][10]. However, other research attempts were conducted to minimize the patient dose during AP pelvis radiographic examination through optimizing its radiographic practice [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the kVp and mAs used were a little bit different from those used in other studies [2,15,10,47].…”
Section: Discussionmentioning
confidence: 93%
“…Several cases raise the level of radiation knowledge in staffs, patients, and physicians. Continuous beam training increases radiation safety and reduces fear of radiation (27,31,32), as well as determining radiation levels and dose level references for each region (17) and monitoring personnel radiation measures are two other effective strategies (33). In our study, it was clearly demonstrated that the dose received in nuclear medicine tests (more than 500 times that of Chest PA) increased the risk of cancer in younger people, especially in vulnerable tissues.…”
Section: Discussionmentioning
confidence: 99%
“…An overall review of the previous study, indicates that radiologists and technologists who are employed in different sections have inadequate information about ionizing beams, or they underestimate its harms (13)(14)(15)(16). All the same, another study claims that reducing the dose level in X-Ray examinations is possible if imaging center staff get appropriate training (17). Today, by spreading information, clienteles of imaging centers inquire about potential perils of "imaging procedures."…”
mentioning
confidence: 99%